The Power of Strong Aroma: The Effects Of Ambient Scent on Traditional Kapurung Food for Customer Impulsive Buying - Fajri, Nofias (Jurnal Serambi Engineering, 2025)
The development of the food UMKM sector has an important role in economic growth. Indonesia has a variety of traditional foods from various regions such as Kapurung. Public interest in traditional foods has decreased because of the tendency of people to consume modern foods that have a more appetizing aroma. The purpose of this study was to create a valid and reliable model that can represent scent ambient on impulsive buying behavior. The data analysis method used the Structural Equation Model PLS method. The results obtained in this study contained one initial hypothesis used in the development of 25 scent ambient items with 70 consumer respondents at the Pugalu Kapurung stall. The time spent (TS) indicator is an indicator that has a significant influence on impulsive buying behavior (IB) with a path coefficient value of 0.795, while the scent ambient variable significantly affects impulsive buying behavior with a path coefficient value of 0.539. The scent ambient variable is influenced by the scent intensity sub variable with a path coefficient value of 0.317. The stimulating indicator has a significant influence on scent intensity with a path coefficient value of 0.153.